Legal Reconstruction of the Implementation Urgency of the Single Identity Number Policy in Indonesia's Public Service - Triyanti, Ninuk (UNISSULA, 2024)
The Population Administration Law mandates that the Population Identification Number (Nomor Induk Kependudukan/NIK) serve as a single identity number for all public service administration in Indonesia. However, the implementation of this policy remains suboptimal, as public service institutions continue to rely on their own data and identification numbers rather than utilizing the NIK. This study aims to examine the implementation of the NIK in implementing population administration and public services in Indonesia. The method used in this study is a literature study, which examines various legal sources, scientific literature, journals, and relevant materials related to NIK. The main emphasis lies on Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration, which is the legal basis for this study. The results indicate that effectively implementing this policy is crucial for establishing more efficient government governance and optimizing public services. Moreover, the single identity number policy embodies the legal ideals of the Indonesian state, grounded in Pancasila values. It aligns with the three primary objectives of law: social benefit, legal certainty, and justice. This study highlights the significant implications of adopting a unified identification system for enhancing governance and service delivery in Indonesia.